Adaptive Factors Influencing Mental Health of Postpartum Mothers - ปานศรี, สุพรรณิกา (Journal of The Royal Thai Army Nurses, 2019)
Abstract This descriptive study aimed to investigate the influences of age, postpartum fatigue, self-esteem, functional status after childbirth, and social support on mental health of postpartum mothers. The sample consisted of 129 postpartum mothers, attending postpartum follow-up for 4-6 weeks at Phramongkutklao Hospital. The research instruments included a personal data interview, Thai Mental Health Indicator, the Rosenberg’s Self-Esteem Scale, the Inventory of Functional Status After Childbirth, the Modified Fatigue Symptom Checklist, and the Multidimensional Scale of Perceived Social Support. Data were analyzed using descriptive statistics, Pearson correlation, and Multiple Linear Regression. The results revealed that 27.9% postpartum mothers had better mental health than general people, while mental health of 59.7% of them was equal to general people. Furthermore, age, postpartum fatigue, self-esteem, functional status after childbirth, and social support together could statistically significantly predict mental health of postpartum mothers by 49.5% (R2 = .495, F = 24.093, p < .001). However, only postpartum fatigue (β = -.205, p < .01), self-esteem (β = .466, p < .001), and social support (β = .257, p < .001) are the key factors that could statistically significantly predict mental health of postpartum mothers. The results suggest that nurse midwives should organize program to promote adaptive responses, self-esteem, and reduce postpartum fatigue by encouraging husbands and relatives for good mental health of postpartum mothers.